An IoT platform for production monitoring in the aerospace manufacturing industry. (25th September 2022) - Rodrigues, Daniel; Carvalho, Paulo; Rito Lima, Solange; Lima, Emanuel; Lopes, Nuno Vasco
Abstract: The current evolution and availability of IoT and CPS technologies is fostering a new industrial revolution, where manufacturing technologies and processes are leveraged by intelligent automation, data exchange and ubiquitous connectivity. In this context, enhancing the control and monitoring of production lines is of particular interest as a crucial management step regarding smart manufacturing and product delivery. Focusing on the demanding field of aerospace industry, the present work proposes an IoT-based solution for improving the quality of monitoring data assisting the production and assembly processes. The proposed architecture prototype integrates: (i) components to extend the manufacturing execution systems (MES); (ii) components of a scalable IoT platform; (iii) components for integrating and analysing production line data; and (iv) a new data visualisation application to assist production control. Aspects such as gathering detailed production data and measuring time per stage along the production lines are provided for controlling and optimising productivity, avoiding potential errors resulting from human-based monitoring methods. Consequently, the proposed solution contributes for a better management of production resources, enabling reduced production time, faster and more informed responses, and enhanced control over the production processes in general.